ANALYSIS OF CORTISOL LEVEL AFTER HIGH-DOSE AND LONG-TERM PREDNISONE EXPOSURE IN CHILDREN WITH STEROID-SENSITIVE NEPHROTIC SYNDROME - Dn, Nani Wijayanti; Zairina, Nun; Asmaningsih, Ninik; Yulistiani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to analyze the cortisol levels in induction and alternate phases associated with the clinical manifestation in the developing of adrenal suppression. Methods: An observational, longitudinal study which had been approved by the ethical committee of Dr. Soetomo Teaching Hospital Surabaya was conducted from June to October 2016. The cortisol levels were measured before induction phase (t=0), after induction phase (t=1), and after alternate phase (t=2). The venous blood samples were obtained in the morning at 08.00–09.00 am. The data were analyzed using student's t-test. Results: A total of 15 patients were included, but 6 patients were excluded because of cross-reactivity with prednisone when using ADVIA Centaur Cortisol Assay. 9 patients (55.56% boys) had a mean age 6–< 12 years old and 33.33% were initial attack and dependent steroid nephrotic syndrome. 8 of 9 patients had a normal cortisol level at baseline (t=0). The cortisol level decrement in the induction phase was 72.92% (11.79±10.66 mcg/dL–1.75±1.08 mcg/dL) (*p=0.024). After alternate phase, the cortisol levels increased 417.60% (1.75±1.08 mcg/dL to 5.95±3.33 mcg/dL (*p=0.007). The clinical manifestation as nausea/vomiting and abdominal distension only appeared in 11.11% of patients in the induction phase but not in the alternate phase. Conclusions: Hypothalamus-pituitary-adrenal (HPA) axis suppression could develop after induction phase which was indicated by low cortisol levels. High-dose and long-term prednisone exposure decreased the cortisol levels reversibly. The clinical manifestation of adrenal suppression as weakness, nausea/vomiting, acute dehydration, and abdominal distension almost did not manifest in all patients.